Remote affective disorders after thrombectomy of thrombotic occlusion: comparative analysis of subjective and objective symptoms - Regush, Andriy; Markova, Marianna (Psychosomatic Medicine and General Practice, 2026)
Background. The work is devoted to the comparison of subjective and objective assessment of long-term affective disorders in patients who underwent thrombectomy of thrombotic occlusion. Study objective. To determine the features of self-perception and the actual presence and severity of affective disorders in patients who underwent thrombotic occlusion thrombectomy in the distant postoperative period. Materials and methods. During 2023-2024, a prospective study of 96 patients who underwent thrombectomy for thrombotic occlusion was conducted at the Center for Roentgen Endovascular Neurosurgery of the Kyiv City Clinical Hospital No. 1 (Kyiv, Ukraine). The study of long-term psychiatric consequences took place in the late postoperative period – on the 30-35th day after surgery using clinical-anamnestic, clinical-psychopathological and psychodiagnostic research methods. An objective assessment of the affective sphere of patients was carried out using the Hamilton Anxiety Rating Scale (HARS), the Hamilton Depression Rating Scale (HDRS) and the Young Mania Rating Scale (YMRS). The Hospital Anxiety and Depression Scale (HADS) and the Altman Self-Rating Mania Scale (ASRM) were also used – diagnostic tools that are based on a subjective assessment of the severity of existing affective disorders. Results. The features of self-perception of existing affective disorders in patients who underwent thrombectomy of thrombotic occlusion in long-term postoperative period were determined. Specific characteristics of self-perception regarding affective disorders were identified in patients who underwent thrombectomy for thrombotic occlusion during the long-term postoperative period. In particular, it was established that there is no significant gap between the objective clinical presentation and the subjective perception of affective disorders among the selected patient population. The observed difference between expert assessment and patient self-reports is minimal, indicating a preserved capacity for reflection on one’s emotional state during the long-term postoperative phase. However, the existing slight discrepancy in indicators is driven by a specific tendency toward aggravation: patients are inclined to exaggerate the intensity of depressive and anxious manifestations. Conclusion. The obtained data on the peculiarities of self-perception of affective disorders in patients who underwent thrombectomy for thrombotic occlusion form the basis for a personalized system of comprehensive rehabilitation of these patients. Key words: ischemic stroke, anxiety, depression, neurosurgery, psychiatry. УДК 616.89-008.45/.47:616.831-005.1-089.87]-036.8-085.851